Response to Emilio Alvarez, “Recovering an Ortho-Missio” - Schroeder, Roger (Missiology, 2026)
This was a response to the plenary address of The Most Rev. Emilio Alvarez, PhD, on the topic of “Recovering an Ortho-Missio: Reimagining Unity and Mission in an Age of World Christianity.” delivered on June 21, 2025, at the annual conference of the American Society of Missiology at St. Mary’s College, Notre Dame, IN.